# trigonometry

posted by .

show that sin 2theta/1-cos 2 theta = cot theta

• trigonometry -

The equation you gave is NOT an identity,

Did you mean

sin (2Ø)/(1 - cos^2 Ø) = 2cotØ ?

LS = 2sinØcosØ/(sin^2 Ø)
= 2cosØ/sinØ
= 2cotØ
= RS

## Similar Questions

2. ### Math

1)Find cos theta if sin theta=3/5 and 90 degrees<theta<180 degrees. A)4/5 B)-4/5 C)square root of 34/5 D)-square root of 34/5 I chose A 2)Simplify:1-csc^2theta/cot^2theta A)-1 B)1 C)tan^2theta D)1/sin^4theta I chose C 3)Simplify:-5(cot^2theta-csc^2theta) …
3. ### Math

There are no typos and no work b/c I don't know how to do them. Thanks. 1)Find cos theta if sin theta=3/5 and 90 degrees<theta<180 degrees. A)4/5 B)-4/5 C)square root of 34/5 D)-square root of 34/5 I chose A 2)Simplify:1-csc^2theta/cot^2theta …
4. ### math

There are no typos and no work b/c I don't know how to do them. Thanks. 1)Find cos theta if sin theta=3/5 and 90 degrees<theta<180 degrees. A)4/5 B)-4/5 C)square root of 34/5 D)-square root of 34/5 I chose A 2)Simplify:1-csc^2theta/cot^2theta …
5. ### Algebra II

Which of the following expressions are not equal to 1?
6. ### Algebra II

Multiple Choice Which expression is NOT equivalent to 1?
7. ### trigonometry

I need help in understanding how to identify which identity to use. using this question as an example. Show that tan theta (sin theta+cot theta cos theata)all over cos theta = sec^2 theta. Please explain.
8. ### Mathamatics

Solve the following trigonometry identities. a) 1-cos2(theta) = sin(theta)cos(theta)/cot(theta) b) (1-cos2(theta))(1-tan2(theta))=sin2(theta)-2sin4(theta)/1-sin2(theta) *its supposed to be cos to the power of two, sin to the power …
9. ### Trigonometry

Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
10. ### Trigonometry

Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions